An approach for home load Energy Management problem in uncertain context - Duy Long Ha; Minh Hoang Le; Ploix, S. (2008 IEEE International Conference on Industrial Engineering and Engineering Management, 2008)
This paper focuses on energy management problem applied to residential sector. The optimizing procedure of energy management is based on the available prediction (weather prediction, user¿s habit etc) which contains the uncertainty and imperfect knowledge. This uncertainty can be modelled as interval model. An approach composing three steps is proposed. Multi-parametric programming is used to calculate the family of an optimal solution. Two examples are proposed to illustrate this approach.